Suprasegmental Errors of Students with Javanese Mother Tongue: A Case at a Private Islamic University in Purworejo - Semi Sukarni; Junaedi Setiyono; Rofiq Nurhadi (Ta'dib: Jurnal Pendidikan Islam, 2020)
This study was aimed to examine errors found in suprasegmentals, more specifically in word stress and intonation; and to explain the causes of errors made by the learners. The research samples were twenty of the first semester students who spoke Javanese as their mother tongue and who took Pronunciation subject. The instruments of the study were pronunciation test and focus group interview. The pronunciation test was used to get the data of suprasegmental errors, specifically in word stress and intonation. Meanwhile, the interview was used to get the data of the causes of errors. The data were analyzed by using descriptive statistics analysis and thematic analysis. The findings showed that there were 35.8 % errors in word stress and 40 % errors in intonation. Then, the source of errors occurred because of mother-tongue influence, target language or intralingua, learning strategy and learners' attitude. Other factors contributed to the errors were lack of practice and lack of exposure to the native speakers both in the classroom and outside the classroom